2022
DOI: 10.2147/cmar.s364761
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Related Noncoding RNAs: Emerging Regulatory Factors of Gastric Cancer

Abstract: Gastric cancer (GC) is one of the most common malignant cancers that seriously affect human health. Autophagy is a highly conserved self-defense mechanism found to plays an important role in the occurrence, progression, drug resistance, and prognosis of GC. Noncoding RNAs (ncRNAs) play a critical role in the occurrence and development of a variety of diseases including GC. In recent years, increasing attention has been given to research on autophagy-related ncRNAs, such as miRNA, lncRNA, and circRNA in GC. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 71 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…A series of studies using apoptosis have been proved to be effective in the prevention and treatment of many diseases including cancer ( Pistritto et al, 2016 ; Xu et al, 2019 ; Berthenet et al, 2020 ). Cell autophagy is a highly conserved self-defense mechanism ( Lu et al, 2022 ). Autophagy plays a key role in the occurrence, development and prognosis of GC ( Cao et al, 2019 ; Wu et al, 2021 ; Lu et al, 2022 ).…”
Section: Effects Of Phytochemicals On the Occurrence And Development ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies using apoptosis have been proved to be effective in the prevention and treatment of many diseases including cancer ( Pistritto et al, 2016 ; Xu et al, 2019 ; Berthenet et al, 2020 ). Cell autophagy is a highly conserved self-defense mechanism ( Lu et al, 2022 ). Autophagy plays a key role in the occurrence, development and prognosis of GC ( Cao et al, 2019 ; Wu et al, 2021 ; Lu et al, 2022 ).…”
Section: Effects Of Phytochemicals On the Occurrence And Development ...mentioning
confidence: 99%
“…Cell autophagy is a highly conserved self-defense mechanism ( Lu et al, 2022 ). Autophagy plays a key role in the occurrence, development and prognosis of GC ( Cao et al, 2019 ; Wu et al, 2021 ; Lu et al, 2022 ). Induction of cell apoptosis and autophagy has been found maybe a pivotal mechanism of the inhibition of the initiation and the development of gastric cancer.…”
Section: Effects Of Phytochemicals On the Occurrence And Development ...mentioning
confidence: 99%
“…Autophagy is a conserved self-defense mechanism that responds to various cellular stresses [16][17][18]. Normal and moderate autophagy is particularly important for cell survival and maintaining homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of autophagy involves the occurrence and development of a variety of diseases, including gastric cancer. Increasing pieces of evidence show that autophagy plays a critical role in the occurrence and development of gastric cancer [17,19,20]. Studies demonstrated that autophagy plays a regulatory role in the occurrence and development of cancer by regulating EMT and abnormal cell proliferation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation